Math Doubts

Find the value of $p$ if quadratic equation is $x^2+px+12 = 0$ and roots are in the ratio $1:2$

$x^2+px+12 = 0$ is the given quadratic equation and the roots of this equation are in the ratio of $1:2$.

Step: 1

If $ax^2 + bx + c = 0$ is the standard form quadratic equation and it represents the given equation. If roots are $\alpha$ and $\beta$, the same roots are also roots of the given equation.

Therefore, $\alpha : \beta = 1:2$

$\implies \dfrac{\alpha}{\beta} = \dfrac{1}{2}$

$\implies \beta = 2 \alpha$

It expresses that the value of $\beta$ is twice the value of $\alpha$.

Step: 2

The summation of the roots and the product of the roots of the quadratic equation can be expressed in terms of the literal coefficients of the standard form quadratic equation.

$\alpha + \beta = \,-\dfrac{b}{a}$

$\alpha \beta = \dfrac{c}{a}$

Compare the quadratic equation $x^2+px+12 = 0$ with standard form quadratic equation. Therefore $a = 1$, $b = p$ and $c = 12$.

$\alpha + \beta = \,-\dfrac{p}{1} = -p$

$\alpha \beta = \dfrac{12}{1} = 12$

Step: 3

According to step $1$, the value of $\beta$ is equal to $2\alpha$. So, eliminate $\beta$ from the product of the roots by substituting its values in terms of $\alpha$.

$\alpha \beta = \alpha (2 \alpha) = 12$

$\implies 2 \alpha^2 = 12$

$\implies \alpha^2 = \dfrac{12}{2}$

$\require{cancel} \implies \alpha^2 = \dfrac{\cancel{12}}{\cancel{2}}$

$\therefore \,\, \alpha^2 = 6$

Step: 4

Similarly, eliminate $\beta$ from the summation of the roots of the quadratic equation by substituting its values in terms of $\alpha$.

$\alpha + 2\alpha = -p$

$\implies 3\alpha = -p$

$\implies \alpha = -\dfrac{p}{3}$

Square both sides.

$\implies \alpha^2 = {\Bigg(-\dfrac{p}{3}\Bigg)}^2$

$\implies \alpha^2 = \dfrac{p^2}{9}$

It is derived in the previous step, the value of $\alpha^2$ is $6$.

$\implies 6 = \dfrac{p^2}{9}$

$\implies 6 \times 9 = p^2$

$\implies p^2 = 6 \times 9$

$\implies p = \pm \sqrt{6 \times 9}$

$\therefore \,\, p = \pm 3 \sqrt{6}$

The values of $p$ are $3 \sqrt{6}$ and $-3 \sqrt{6}$.

It is the required solution for this quadratic equation problem in mathematics.



Follow us
Email subscription
Math Doubts
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Mobile App for Android users Math Doubts Android App
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more